Neural mechanisms of bilateral deficit in maximal force production in specific groups of athletes - Skarabot, Jakob (2016)
The mechanisms of bilateral deficit (BLD) have been studied extensively, but remain obscure. Neural mechanisms have been proposed, including interhemispheric inhibition (IHI). In this study specific groups of athletes who were more likely to exhibit BLD or bilateral facilitation (BLF) were compared with controls. If IHI is truly the underlying cause of BLD it is of interest whether the nature of IHI is reflected in the magnitude of BLD. 20 male subjects (ALL) were split into three groups according to the nature of their activity: bilateral, unilateral and control. Additionally, they were split into two groups whether they exhibited BLD or BLF. Maximal unilateral (UL) and bilateral (BL) isometric knee extensions were performed while receiving electrical stimulation of the femoral nerve and both contralateral and ipsilateral transcranial magnetic stimulation. Main variables of interest included bilateral index in force and EMG activity, voluntary activation level, motor evoked potentials of target and ipsilateral muscles (MEPs), and cortical and ipsilateral silent periods. Significant BLD was observed for ALL (BI = -8.76 ± 13.43, p = 0.009), but not for any of the separate groups. No BLD was noted in EMG activity and no parallelisms between force and EMG was found. Voluntary activation level was significantly higher during BL compared to UL contractions (~ 97% vs. 93%, p = 0.045), with no differences between groups. MEPs during BL were significantly bigger (p = 0.042, and p = 0.005, respectively) than during UL contractions with no differences between groups. No differences in silent periods were noted regardless of grouping. Variability of BLD observed was likely due to poor testing specificity. Based on unaltered silent periods, BLD may not be related to inhibition at the cortical level. Conversely, higher values of voluntary activation level and motor evoked potentials during BL when compared to UL contractions may indicate involvement of cortical facilitation.